Mikhail Gorbachev's First Visit to Britain: 30 Years on - K. V. Shlykov (Vestnik MGIMO-Universiteta)
The article explores the significance of Mikhail Gorbachev's first journey to the UK in December 1984 for the East-West relations. The visit was initiated by Margaret Thatcher who wanted to get acquainted with the potential Soviet leader as she hoped to become a trusted intermediary between Moscow and Washington. The revitalization of contacts with the USSR was a part of Britain's resurgence as a major world player after the Falklands victory. The discussions in London focused on the issue of strategic stability, though they could only serve to give the parties a better understanding of each other's position, as no political agreement could be reached due to the nature of the visit and the fact that any agreement on the subject had to be between the Soviet Union and the United States. The bilateral relations issues being discussed included mostly economic cooperation and such problems as human rights in the USSR and Soviet assistance to the British miners' strike. Gorbachev's speech on "new political thinking" and "a common European home", expressions first used during the visit to Uk, rang hollow to London, however Thatcher had the impression that she could deal with the Soviet politician in future. The British public opinion also saw Mikhail Gorbachev and his wife favourably. Later statements of Lady Thatcher and Gorbachev's critics on the meeting being defining for the foreign policy of the perestroika era should be seen as exaggerated, as the demise of the Communist system and the USSR were not foreseen by anyone in 1984, either in London or in Moscow.